Final ORBIS project conference - Skotnicki, Marcin; Lulek, Janina (Journal of Medical Science, 2023)
We are pleased to present this Journal of Medical Sciences issue, entirely dedicated to the final ORBIS (Open Research Biopharmaceutical Internships Support) project conference. The Final ORBIS Conference took place on 5–6 July 2023 at Poznan University of Medical Sciences (Poznan, Poland). The conference summarized the activities of the five‑year ORBIS project (e936), which received funding of EUR 2.27 million under the Marie Sklodowska‑Curie Actions, Research Innovation Staff Exchange of the Horizon 2020 framework program (H2020-MSCA‑RISE, no. 778051). Poznan University of Medical Sciences coordinated this international and cross‑sectoral project with fourteen academic institutions and pharmaceutical companies from eight countries. The goal of ORBIS was research and training cooperation between universities and the industry sector to develop better, more effective, modern drugs. ORBIS implemented these ideas through international internships of scientists and PhD students to partner institutions (450 months in total). The Final ORBIS Conference was an opportunity to celebrate this success. During the conference, scientists and specialists from European and American centers were given plenary lectures on the most current topics of modern pharmaceutical sciences, including preformulation (e878, e908, e901) and formulation studies (e893, e859, e914, e926) as well as challenges in the new therapies (e925, e907, e903) and regulatory policies (e890). There were also speeches presenting the scientific effects of completed internships, delivered by participants from the project consortium. After the conference, the scientific committee invited all lecturers to submit their papers to this Journal of Medical Sciences issue. This issue includes all submitted and accepted papers, each providing substantial new material beyond the original conference version. We thank the authors and reviewers of these papers for their efforts in producing and reviewing these papers within the strict time limits imposed by this issue’s publication constraints. We also gratefully acknowledge the support of the JMS editors‑in‑chief (Prof. Jarosław Walkowiak and Prof. Adrianna Mostowska) and the editorial office.